Intermediate state representation approach to physical properties of molecular electron-detached states - II. Benchmarking - Dempwolff, Adrian; Paul, Alexander C.; Belogolova, Alexandra M.; Trofimov, Alexander B.; Dreuw, Andreas (The journal of chemical physics, 2020)
The third-order algebraic-diagrammatic construction method for studies of electron detachment processes within the electron propagator framework [IP-ADC(3)] was extended to treat the properties of molecular states with a detached electron using the intermediate state representation (ISR) formalism. The second-order ISR(2) equations for the one-particle (transition) density matrix have been derived and implemented as an extension of the IP-(U)ADC(3) method available in the Q-CHEM program. As a first systematic test of the present IP-(U)ADC(3)/ISR(2) method, the dipole moments of various electronic states of closed- and open-shell molecules have been computed and compared to full configuration interaction (FCI) results. The present study employing FCI benchmarks also provides the first rigorous estimates for the accuracy of electron detachment energies obtained using the IP-ADC(3) method.
Gesehen am 14.04.2020